2006
DOI: 10.2165/00002018-200629060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Dose Adaptation of Antineoplastic Drugs in Patients with Liver Disease

Abstract: Dose adaptation for liver disease is important in patients treated with antineoplastic drugs because of the high prevalence of impaired liver function in this population and the dose-dependent, frequently serious adverse effects of these drugs. We classified the antineoplastic drugs marketed in Switzerland at the end of 2004 according to their bioavailability and/or hepatic extraction to predict their kinetic behaviour in patients with decreased liver function. This prediction was compared with kinetic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…Some physicians may argue that procedural intervention for biliary decompression is not necessary in lymphoma patients who present with obstructive jaundice because chemotherapy will lead to rapid resolution of the biliary obstruction [23]. However, administering chemotherapy to lymphoma patients with obstructive jaundice may enhance the risk profile of many chemotherapeutic agents particularly those with high hepatic extraction like doxorubicin and vinblastine [5]. While the risk reward profile of biliary decompression in this setting is not well defined, our institutional bias is to favor early decompression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some physicians may argue that procedural intervention for biliary decompression is not necessary in lymphoma patients who present with obstructive jaundice because chemotherapy will lead to rapid resolution of the biliary obstruction [23]. However, administering chemotherapy to lymphoma patients with obstructive jaundice may enhance the risk profile of many chemotherapeutic agents particularly those with high hepatic extraction like doxorubicin and vinblastine [5]. While the risk reward profile of biliary decompression in this setting is not well defined, our institutional bias is to favor early decompression.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, lymphoma accounts for 5% of new cancer cases and 3.6% of cancer deaths annually. Obstructive jaundice, a rare complication of lymphoma, can accompany the initial presentation of lymphoma or develop later in the course of the disease [5]. Obstructive jaundice can also indicate recurrent disease in a patient with a history of lymphoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with greater transaminase elevations before HSCT were reported to have a higher incidence of severe SOS than those with minimal elevations [7]. Several other prospective studies have also reported an association between pretransplant transaminase elevations and subsequent development of SOS [9,10,12]. These studies also reported a marginal statistical significance for correlation between severe SOS and a remote history of hepatitis, drug-related liver injury, or abdominal radiation therapy [7].…”
Section: Potential For Liver Toxicity Post-transplant Sinusoidal Obstmentioning
confidence: 97%
“…However, the literature consists of mostly case reports including patients with only moderate liver dysfunction. In addition, administration guidelines have focused on patients with liver cirrhosis or fibrosis and not on patients with increased transaminases and/or cholestasis [12]. Therefore, the available pharmacokinetic data are far from complete.…”
Section: Pharmacokinetic Considerations In Patients With Liver Diseasesmentioning
confidence: 99%